Multiple neural fibrolipomas with macrodactyly - Aparna Gupta; V Geetha; Vidya Monappa; Sudha S Bhat (Wolters Kluwer Medknow Publications, 2011)
Neural fibrolipoma is an uncommon tumor-like lesion that involves the upper extremity and usually arises in the median nerve. It is associated with macrodactyly in one-third of the cases. A 3-year-old girl presented with increasing size of fingers of both the hands since birth. Clinical examination revealed macrodactyly of two fingers of the right hand and three fingers of the left. Surgical reduction was performed and microscopy of the biopsy specimen established the diagnosis of neural fibrolipoma. Knowledge of the clinicopathological features is necessary for accurate diagnosis and treatment of this rare entity.